2008
DOI: 10.1074/jbc.m802623200
|View full text |Cite
|
Sign up to set email alerts
|

Use of Akt Inhibitor and a Drug-resistant Mutant Validates a Critical Role for Protein Kinase B/Akt in the Insulin-dependent Regulation of Glucose and System A Amino Acid Uptake

Abstract: Protein kinase B (PKB)/Akt has been strongly implicated in the insulin-dependent stimulation of GLUT4 translocation and glucose transport in skeletal muscle and fat cells. Recently an allosteric inhibitor of PKB (Akti) that selectively targets PKB␣ and -␤ was reported, but as yet its precise mechanism of action or ability to suppress key insulin-regulated events such as glucose and amino acid uptake and glycogen synthesis in muscle cells has not been reported. We show here that Akti ablates the insulin-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 51 publications
10
89
0
Order By: Relevance
“…This inhibitor interacts with the pleckstrin homology domain of Akt preventing the conformational change required for phosphorylation of this kinase (Green et al, 2008). As shown in Fig 7, even high concentrations of this inhibitor (50μM) do not have any effect on MC5R-mediated ERK1/2 phosphorylation after α-MSH stimulation.…”
Section: Signaling Requirements For Mc5r-mediated Erk1/2 Activationmentioning
confidence: 86%
“…This inhibitor interacts with the pleckstrin homology domain of Akt preventing the conformational change required for phosphorylation of this kinase (Green et al, 2008). As shown in Fig 7, even high concentrations of this inhibitor (50μM) do not have any effect on MC5R-mediated ERK1/2 phosphorylation after α-MSH stimulation.…”
Section: Signaling Requirements For Mc5r-mediated Erk1/2 Activationmentioning
confidence: 86%
“…Studies report that TNFα has both neuroprotective and neurotoxic effects depending on the receptor subtype [44]. The involvement of TNFα-R 1 is associated with the inhibition of hippocampal plasticity and also promotes apoptosis [14]. Furthermore, TNF α modulates NF-κβ up-regulation which has been linked to deficits in spatial memory [45].…”
Section: Discussionmentioning
confidence: 99%
“…Tuzcu et al has demonstrated that administration of antioxidants such as vitamin E and quercetin improves memory formation in streptozotocin induced diabetic rats [12]. C-reactive protein (CRP) and diabetes associated inflammatory cytokines such as tumour necrosis factor (TNF α) alter hippocampal synaptic plasticity and have been shown to be neurotoxic [14]. Furthermore, the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and N-methyl-D-aspartate (NMDA) receptors responsible for memory formation are modified and impaired in streptozotocin-induced diabetic rats [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing precedent for development of allosteric kinase inhibitors, which have proven to be much more selective than classical ATP competitive inhibitors (21,(43)(44)(45)(46)(47)(48)(49). Allosteric modulation of kinases is particularly promising because many soluble kinases have inter-or intradomain associations that allosterically regulate kinase activity.…”
Section: Discussionmentioning
confidence: 99%